Alumni Association in Washington DC this week - Uribes, Tom::::::::: (2013)
The Fresno State Alumni Association will sponsor a reception for Beltway-area Bulldogs in Washington D.C. with President Joseph I. Castro and Dr. Peter Smits, vice president for Advancement.